THE CAREER ENGAGEMENT OF BPK RI EMPLOYEES AFFECTED BY CAREER ADAPTABILITY AND PROMOTABILITY - arlina, devi (Jurnal PubBis, 2022)
This study aims to know about the effect of promotability mediation on career adaptability and career engagement of BPK RI employees. There were 298 employees who became respondents in this research, most of them were in Auditor Functional Grade. The measurement was conducted by questionnaires using Carier Adaptability Scales (CAAS) developed by Savickas & Porfeli (2012) to measure career adaptabilities, four-item scales based on previous study by Tolentino, Garcia, Restubog, Bordia, and Tang (2013) to measure promotability, and Career Engagement Scale (CES) developed by Hirschi, Freund, and Herrmann (2014) to measure career engagement. The questionnaires were distributed online by giving link to fill google form. The answers from respondents were processed using Lisrel and SPSS. This research was expected to provide insight regarding the impact of career adaptabilities and promotability on the level of career engagement. The result of this research showed that career adaptability and promotability were positively and significantly related to career engagement of BPK RI employees.